Clinical Spectrum and Outcome in Children Presenting with Empyema Thoracis in Tertiary Care Hospital: Role of Intrapleural Streptokinase - Sadia Qasim, Tahira Aslam, Afsheen Batool Raza (Pakistan Journal of Medical & Health Sciences, 2023)
Aims and Objectives: To correlate clinical symptoms of empyema thoracis with treatment outcome. To analyze role of intra-pleural streptokinase in Empyema thoracis. Material and Methods: This cross sectional study was carried out at the department of pediatric medicine unit, UCHS and The Children Hospital, Lahore, spanning from December 10, 2022, to June 9, 2023. Non-Probability, Consecutive sampling technique was used. A total of 70 children who met the inclusion criteria were enrolled in the study. The patients were classified based on their need for various treatment options such as IV antibiotics with chest tube drainage, intrapleural streptokinase, and decortication surgery. The data was inputted and analyzed using SPSS version 25, stratified by age and gender in relation to treatment outcomes. A significance level of p≤0.05 was deemed as significant. Results: Of these 70 study cases, 55(78.6%) were male patients and 15(21.4%) were female patients. Mean age of our study cases was 7.6±4.6 years. According to clinical spectrum of empyema thoracis distribution, 70(100.0%) had fever, 59(84.3%) had respiratory distress, 61(87.1%) had cough, 42(60.0%) had hemoptysis and 32(45.7%) had chest pain. Conclusion: Prompt recognition and appropriate management of pneumonia can avert the progression to empyema. Utilizing antibiotics alongside chest tube placement and administration of streptokinase has shown to be a successful approach in addressing pyogenic empyema thoracis in children residing in resource-limited environments. Keywords: Parapneumonic Effusion, Complications, Clinical Spectrum, Outcome, Chest Tube.